Bioremediation of contaminated river sediment and overlying water using biologically activated beads: A case study from Shedu river, China. (January 2020) - Fu, Dafang; Yan, Yixin; Yang, Xinde; Rene, Eldon R.; Singh, Rajendra Prasad
Abstract: The main aim of this work was to test in-situ sediment remediation of a polluted river bed by the addition of biologically activated beads. The factors influencing the bioremediation performance were analyzed and compared in four experimental devices (D1: 230 g beads without microbes; D2: 230 g detached microbes (20%); D3: 230 g microbial beads; and D4: 230 g activated carbon and microbes). Device 3 (microbial beads) showed the best pollutant removal performance for NH4 + -N: 76.3%, TN: 93.3% and COD: 92.8%, respectively, in the overlying water. The TOC, TN, heterotrophic and sulfide oxidizing bacteria removal rates reached were 61.9%, 58.0%, 45%, and 90%, respectively. Graphical abstract: Image 1 Highlights: Overlying water and in-situ sediment bioremediation experiments were performed. Factors: temperature 25–30 °C, DO 2.0–3.0 mg/L, pH 7.0–8.0 and C/N ratio 10-15. Parameters: NH4 + -N, TN, TOC, COD and heterotrophic/sulphur bacteria counts. Immobilized activated beads are very efficient for river sediment remediation.